How do-more-good frames influence climate action likelihood and anticipated happiness - Radke, Jade; Guan, Sophia; Dunn, Elizabeth; Zhao, Jiaying (Frontiers in Communication, 2026)
Calls for climate action often emphasize the need to reduce harm, such as by eating less meat, driving less, and shopping less. A more productive approach, however, may be to encourage people to do more good. To compare the two approaches, we conducted two pre-registered online experiments in which participants were randomly assigned to either a do-more-good condition or a do-less-bad condition. The do-more-good condition presented 15 actions framed so that doing more of each action would benefit the environment (e.g., reuse, repair, recycle, or repurpose all of your items). In the do-less-bad condition, the 15 actions were framed so that doing less of each action would benefit the environment (e.g., do not throw away any of your items). In Experiment 1 (N = 779), participants were more likely to take climate action and felt happier about doing so in the do-more-good condition than in the do-less-bad condition. Experiment 2 (N = 770) replicated these results. Exploratory analyses revealed the effects of do-more-good frames differed depending on the action. These findings provide implications for climate communication, suggesting that calls for certain climate actions may benefit from encouraging desired behaviors rather than discouraging undesired behaviors.